Absorption of CO2 in biogas with amine solution for biomethane enrichment - Kamopas W. (2017)
© 2016 Published by ITB Journal Publisher. Biogas upgrading with carbon dioxide absorption in a column of monoethanolamine (MEA) solution was carried out. The effects of controlled parameters on the CO 2 absorption such as gas flow rate, solution concentration, height to diameter ratio of the column were considered. High CH 4 concentration could be achieved at low gas flow rate and high MEA concentration. The CH 4 concentration could be up from 70-75% to 92-95% by volume for 0.2 M MEA. A set of breakthrough curves was obtained to determine the absorption characteristics, such as the absorption constant (k), the absorption time when the CO 2 concentration at the outlet was 50% of the concentration at the inlet (τ), and the absorption period (t * ) when the CH 4 concentration was over 90%. An empirical equation of the methane enrichment with the related parameters was developed.